3D printing for tissue engineering in otolaryngology. (3rd March 2020) - Di Gesù, Roberto; Acharya, Abhinav P.; Jacobs, Ian; Gottardi, Riccardo
ABSTRACT: Airway and other head and neck disorders affect hundreds of thousands of patients each year and most require surgical intervention. Among these, congenital deformity that affects newborns is particularly serious and can be life-threatening. In these cases, reconstructive surgery is resolutive but bears significant limitations, including the donor site morbidity and limited available tissue. In this context, tissue engineering represents a promising alternative approach for the surgical treatment of otolaryngologic disorders. In particular, 3D printing coupled with advanced imaging technologies offers the unique opportunity to reproduce the complex anatomy of native ear, nose, and throat, with its import in terms of functionality as well as aesthetics and the associated patient well-being. In this review, we provide a general overview of the main ear, nose and throat disorders and focus on the most recent scientific literature on 3D printing and bioprinting for their treatment.